2021
DOI: 10.15244/pjoes/127555
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Kuznets Curve (EKC) in Australia: Evidence from Nonlinear ARDL Model with a Structural Break

Abstract: In this study, whether economic growth leads to environmental degradation in Australia is analyzed since Australia has been growing consecutively for the last 28 years and is among the countries which are heavily dependent on fossil fuels for energy demands such as oil and coal. In this study, we aim to analyze the EKC hypothesis and the relationships between gross domestic product per capita (GDP in constant 2010 US$), carbon dioxide emissions (CO 2 in metric tons per capita), energy consumption (ENE in kg of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 21 publications
(22 reference statements)
2
14
0
Order By: Relevance
“…He found the positive effects of income and energy use on the CO 2 emissions. This result is shared by other authors, such as the study of (Ang, 2007b;Soytas, Sari, Ewing, 2007;Sotyas, Sari, 2009;Bhat, 2018;Muhammad, Khan, Rehan, 2020;Cihan, Emrah, 2021;Gessesse, He 2020;Zhang, Jihuan, 2021).…”
Section: Literature Reviewsupporting
confidence: 63%
“…He found the positive effects of income and energy use on the CO 2 emissions. This result is shared by other authors, such as the study of (Ang, 2007b;Soytas, Sari, Ewing, 2007;Sotyas, Sari, 2009;Bhat, 2018;Muhammad, Khan, Rehan, 2020;Cihan, Emrah, 2021;Gessesse, He 2020;Zhang, Jihuan, 2021).…”
Section: Literature Reviewsupporting
confidence: 63%
“…Sinha et al [ 18 ] discussed the relationship between energy use isolation and environmental degradation in N-11 countries, and showed that for these countries the relationship between income and carbon emissions is an N-shaped model, not an inverted U-shaped model. After studying the relationship between Australian GDP and carbon dioxide, Özden and Beşe [ 19 ] did not find a significant relationship between GDP and the square of GDP and carbon dioxide, indicating that the EKC hypothesis is not valid.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Purcel suggested that developing and transitional economies should contribute more efforts for climate change to support developed countries. Özden and Beşe (2021) analyzed the EKC hypothesis in Australia by linear and nonlinear cointegration models. Özden and Beşe did not confirm the EKC hypothesis in Australia.…”
Section: Review Of Literaturementioning
confidence: 99%